From Recipe to Being: Philosophical Intertextuality in Rosario Castellanoss Cooking Lessons (Global Journal of Human-Social Science, 2025)
This paper explores some threads of the broad network of intertextual relationships that Lecciones de cocina Kitchen Lessons by Mexican writer Rosario Castellanos establishes with the problem of intersubjectivity and selfawareness within the context of Simone de Beauvoir s existentialist philosophy Through the technique of the protagonist s stream of consciousness and the use of a recipe format to structure the narrative Castellanos reveals how women s identity is shaped by socio-cultural expectations that create a kind of prescribed and preordained essence dictated by the power structures of an androcentric society Lecciones de cocina engages in an intertextual dialogue with Beauvoir s The Second Sex which analyzes the situation of women in a patriarchal society where they have historically been defined and differentiated in relation to men Men are seen as the subject the essential the absolute while women are seen as the object the relative the Other and have been taught to perceive themselves through the male gaze The intertextual relationships in Lecciones de cocina with Beauvoir s existentialist philosophy are not explicit but suggest a deeper integration reflected in the subtext of a narrative that through the architext or the relationship between the text and the genre of the recipe implies a deconstruction that undermines the ideological assumptions of the traditional gender roles assigned to women
Keywords: intertextuality; existentialism; simone de beauvoir; gender roles; women’s identity rosario castellanos